Comparison of pre- and intraoperative findings in 35 cats and 60 dogs presenting with gastrointestinal signs - Kneissl, Sibylle M.; Prüllage, Maria Laura; Vali, Yasamin; Vodnarek, Jakub; Klang, Andrea; Dolezal, Marlies; Strohmayer, Carina (Frontiers in Veterinary Science, 2025)
IntroductionThis retrospective study compared preoperative imaging and intraoperative findings in 35 cats and 60 dogs undergoing laparotomy.ObjectivesThe objective of this study was to evaluate the agreement between preoperative imaging and intraoperative findings in cats and dogs presenting with gastrointestinal signs.MethodsThe medical archive of the teaching hospital was searched from 2021 to 2022 for dogs that presented with gastrointestinal signs. Only animals with preoperative imaging and laparotomy reports within 48 h were included and reviewed. The main imaging and surgical findings were extracted and classified as either ‘agreement’ or ‘no agreement’. Patients with incomplete or vague information were excluded. Additionally, the modality used for preoperative diagnosis (plain radiography, barium study, ultrasonography, computed tomography [CT], endoscopy) and the outcome (discharged, dead) were recorded. Agreement was assessed using Cohen’s kappa statistic. The sensitivity and pretest probabilities of preoperative imaging were calculated using the surgical report as the reference standard.ResultsAgreement between the main imaging and surgical findings was achieved in 84 of 95 cases (88%). No agreement was noted in 11 patients (12%), of which 9 cases were false negative, and two cases were wrongly interpreted. Modalities used for preoperative imaging were ultrasonography (52%), plain radiography (42%), barium study (3%), CT (2%), and endoscopy (1%). Cohen’s kappa was 0 (p = not available) for sonography and 1 (p < 0.001) when using plain radiography. Sensitivity across all modalities, sonography, and plain radiography was 90.3, 81.6, and 100%, respectively, and corresponding pretest probabilities were 97.9, 100, and 95%. Eighty-two animals were discharged, and 13 patients either died or were euthanized.ConclusionThe clinical relevance of this work is providing evidence-based data on errors (no agreement) in preoperative imaging for patients with gastrointestinal disease. Radiography had significantly higher agreement with surgical findings compared to ultrasonography in dogs and cats presenting with gastrointestinal symptoms.